The soil and land classification system of Munanese Farmers in Muna Island, Southeast Sulawesi, Indonesia - Namriah; Badayos, Rodrigo B. (2007)
The Munanese practice of classifying soil was compared with the Soil Taxonomy Framework, while the land evaluation system used by farmers for crop allocation was compared with the Food and Agriculture Organization (FAO) Land Evaluation Framework. The study utilized secondary data obtained from various sources. Primary data were also used and were collected following standard procedure. Field immersion and key informant interviews were conducted to obtain an in-depth understanding about farmers' practices and their strategy for decision making. Farmers identified four soil/land units, namely: wite m bera, wite mbali, wite wongko kapute and wite wongko kaghito. To group soil/land units, farmers used soil color ("red soil"), land use ("all crops can grow"), texture ("white easily-cultivated soil") and workability ("black easily-cultivated soil"). In the Munanese system, the name of the soils incorporated the criteria referred to in the classification. By comparison with the Soil Taxonomy Framework, wite mbera was classified as Typic Eutrustox, wite wongko kapute as Kanhaplic Haplustalfs and wite wongko kaghito as Typic Haplustolls. Wite mbali, another local soil name consisting of two separate groups, was classified as Typic Kandiustox and Kanhaplic Haplustults, respectively. The system has guided Munanese farmers in the selection of crops suitable for the different land units in the community. Their insights on crop requirements relative to the characteristics of the classified land units have guided their approach to farm management.
Keywords: Soil physical chemistry; Classification